Basic Principles and Steps of Types of Software Models - Kaur, Ramanpreet; Singh, Satnam; singh, Harvinder; *, Divya (IJRDO -Journal of Computer Science Engineering, 2017)
Software development life cycle (SDLC) is a methodby which quality software can be developed in the given time andaccording to the customer expectations. SDLC ensures qualityproduct. Software Development Life Cycle Models areframeworks used to design, develop and test the software. Theydefine a set of guidelines which are to be followed during thedevelopment. These models make sure that the software isdesigned systematically, according to the need of the customerand within the time schedule. Different types of softwaredevelopment life cycle models are waterfall, iterative, V-shaped,prototype and spiral model. Each of these models has its ownbenefits and drawbacks